Waves and Magnetism in the Solar Atmosphere (WAMIS) - Ko, Yuan-Kuen; Moses, John D.; Laming, John M.; Strachan, Leonard; Tun Beltran, Samuel; Tomczyk, Steven; Gibson, Sarah E.; Auchère, Frédéric; Casini, Roberto; Fineschi, Silvano; Knoelker, Michael; Korendyke, Clarence; et al. (Frontiers in Astronomy and Space Sciences, 2016)
Comprehensive measurements of magnetic fields in the solar corona have a long history as an important scientific goal. Besides being crucial to understanding coronal structures and the Sun’s generation of space weather, direct measurements of their strength and direction are also crucial steps in understanding observed wave motions. In this regard, the remote sensing instrumentation used to make coronal magnetic field measurements is well suited to measuring the Doppler signature of waves in the solar structures. In this paper, we describe the design and scientific values of the Waves and Magnetism in the Solar Atmosphere (WAMIS) investigation. WAMIS, taking advantage of greatly improved infrared filters and detectors, forward models, advanced diagnostic tools and inversion codes, is a long-duration high-altitude balloon payload designed to obtain a breakthrough in the measurement of coronal magnetic fields and in advancing the understanding of the interaction of these fields with space plasmas. It consists of a 20 cm aperture coronagraph with a visible-IR spectro-polarimeter focal plane assembly. The balloon altitude would provide minimum sky background and atmospheric scattering at the wavelengths in which these observations are made. It would also enable continuous measurements of the strength and direction of coronal magnetic fields without interruptions from the day-night cycle and weather. These measurements will be made over a large field-of-view allowing one to distinguish the magnetic signatures of different coronal structures, and at the spatial and temporal resolutions required to address outstanding problems in coronal physics. Additionally, WAMIS could obtain near simultaneous observations of the electron scattered K-corona for context and to obtain the electron density. These comprehensive observations are not provided by any current single ground-based or space observatory. The fundamental advancements achieved by the near-space observations of WAMIS on coronal field would point the way for future ground based and orbital instrumentation.